FACTORS AFFECTING FINANCIAL STATEMENT FRAUD WITH CORPORATE GOVERNANCE AS A MODERATING VARIABLE (STUDY ON PUBLIC ACCOUNTING FIRMS IN JAKARTA) - Amalia, Gesty; Afrizon (Jurnal Magister Akuntansi Trisakti, 2024)
Abstract. Cases of fraud that occurred in various countries imply that fraud is still common in companies and governments. The purpose of this study is to analyze the factors that influence the Fraud Financial Statement with Corporate Governance as a moderating variable. This type of research includes hypothesis testing using primary data in the form of a questionnaire with the research subject being an accountant registered as a member of the Indonesian Institute of Certified Public Accountants in Jakarta. The samples obtained were 110 respondents. Data is processed using SPSS. Methods of data analysis using multiple regression. The research results conclude that pressure has a positive effect on financial statement fraud; Competence has a positive effect on Financial statement fraud; Arrogance has a positive effect on Financial statement fraud; Integrity has a positive effect on Financial statement fraud; Corporate governance strengthens the influence of pressure on financial statement fraud; Corporate governance strengthens the influence of Competence on Financial statement fraud; Corporate governance weakens the influence of Arrogance on Financial statement fraud; and Corporate governance weakens the influence of integrity on financial statement fraud.